2014
DOI: 10.1111/chso.12072
|View full text |Cite
|
Sign up to set email alerts
|

Space, People, Interventions and Time (SPIT): A Model for Understanding Children's Outdoor Play in Post‐Disaster Contexts Based On a Case Study from the Triple Disaster Area of Tohoku in North‐East Japan

Abstract: Play in the outdoor environment is important for children as part of their childhood and is particularly important for children in a post‐disaster situation. This article explores issues around outdoor play opportunities in the Tohoku region of north‐east Japan, 13 months after the triple disaster of earthquake, tsunami and nuclear power plant failure. A model of space, people, interventions and time (SPIT) is used to understand the situation in this unique case study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 7 publications
(13 reference statements)
0
15
0
Order By: Relevance
“…Some sites have a volunteer play program but most sites hold these activities inside in a meeting room, not outside. It is proposed that in such circumstances, four key factors affecting play—space, people, intervention and time—should be considered for the betterment of children’s environments (Woolley and Kinoshita, 2014) [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some sites have a volunteer play program but most sites hold these activities inside in a meeting room, not outside. It is proposed that in such circumstances, four key factors affecting play—space, people, intervention and time—should be considered for the betterment of children’s environments (Woolley and Kinoshita, 2014) [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…Initially, there was no public program to provide playgrounds and promote children’s play for their health. One year after the disaster, children in temporary housing had little, if any, play space (Woolley and Kinoshita, 2014) [ 10 ]. Four important factors in support of children’s play were identified: Space, People, Interventions and Time.…”
Section: Introductionmentioning
confidence: 99%
“…Some sites have a volunteer play program but most sites hold these activities inside in a meeting room, not outside. It is proposed that in such circumstances, four key factors affecting play-space, people, intervention and time-should be considered for the betterment of children's environments (Woolley and Kinoshita, 2014) [10].…”
Section: Play Car-mobile Playmentioning
confidence: 99%
“…This article discusses a project that explored the design of video games for hospitalized children. It relates to a body of research that has shown how play has therapeutic properties for children’s health and well-being, particularly in times of adversity such as natural disasters (Bateman et al, 2013; Mutch, 2014; Walker et al, 2010; Woolley and Kinoshita, 2014) and hospital settings (Tonkin, 2014; Weldon and Peck, 2014). Given this established connection between play and well-being, the project discussed in this article started with the premise that there would likely be benefits in designing play specifically for children living in adverse contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Given this established connection between play and well-being, the project discussed in this article started with the premise that there would likely be benefits in designing play specifically for children living in adverse contexts. This was considered especially pertinent at the time of the project because children living in adverse conditions, such as after large-scale natural disasters, are often left without play equipment (Woolley and Kinoshita, 2014) or, in the case of hospitalized children, using digital games that were not designed specifically to meet their needs.…”
Section: Introductionmentioning
confidence: 99%